ON THE STRUCTURE OF OXIDE MELTS: DOI: https://doi.org/10.17721/1728-2209.2024.1(59).9 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
A review of experimental X-ray diffraction data on the structure of welding flux melts has been performed. It is shown that the structure factors (SF) of the investigated melts obtained from the diffraction data are similar, regardless of differences in their chemical composition. This indicates that the structure of oxide melts is based on certain atomic clusters with a similar local atomic order. It is shown that such clusters are dense non-crystalline packings of oxygen atoms, which play the main role in forming the structure of welding flux melts. The structural model of oxide melts that is consistent with the high-temperature X-ray diffraction data has been considered. According to this model, nano-sized clusters of oxygen atoms (nanoclusters) with dense packing are uniformly located in a medium ("quasi-gas"), which is characterized by less dense atomic packing and much smaller sizes of atomic clusters. The dense packing of oxygen atoms in such nanoclusters has octahedral and tetrahedral voids, which are partially occupied with cations. Small cations (Si4+) occupy tetrahedral voids, while large cations (Mg2+, Mn2+, Fe2+) occupy only octahedral voids. The Al3+ cations can occupy both tetrahedral and octahedral voids.
Keywords: oxide melts; high-temperature XRD; local atomic structure; model of fluxes melts